The Argentine University against COVID-19: Old and New Discussions in an Unforeseen Reality - Marquina, Monica (International Higher Education, 2020)
During the COVID-19 quarantine, old and new discussions emerged regarding virtual higher education. Under the current state of emergency, the University of Buenos Aires has postponed the start of the academic year from April to June out of concern for quality and social responsibility. Meanwhile, the vast majority of higher education institutions keeps supporting the right to education through distance teaching.